2014
DOI: 10.1111/meca.12047
|View full text |Cite
|
Sign up to set email alerts
|

Redistribution in a Neo‐Kaleckian Two‐country Model

Abstract: We investigate the interaction between demand-driven growth and income distribution in open economies, by combining expenditure-switching and demand spillover effects in a neo-Kaleckian two country model. First, we specify elasticities of wage share and real exchange rate to the money wage relative to labor productivity, in order to precisely describe the distributive pass-through from money wages to the labor share and the real exchange rate. Second, we analyze the demand effects of an increase in the money w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 33 publications
2
17
0
Order By: Relevance
“…On the other hand, Hein and Vogel (2009) and Stockhammer and Onaran (2012) have found wage-led results. Nikiforos and Foley (2012) have shown that non-linearities are of great importance, while Rada and Kiefer (2015) find empirically that, in accordance with numerical results by von Arnim et al (2014), global demand looks wage-led even though individual countries appear to be profit-led. From a theoretical standpoint, whether demand and growth are wage-led or profit-led (or neither) in the short run depends on the shape of the investment function.…”
Section: Related Literaturesupporting
confidence: 57%
“…On the other hand, Hein and Vogel (2009) and Stockhammer and Onaran (2012) have found wage-led results. Nikiforos and Foley (2012) have shown that non-linearities are of great importance, while Rada and Kiefer (2015) find empirically that, in accordance with numerical results by von Arnim et al (2014), global demand looks wage-led even though individual countries appear to be profit-led. From a theoretical standpoint, whether demand and growth are wage-led or profit-led (or neither) in the short run depends on the shape of the investment function.…”
Section: Related Literaturesupporting
confidence: 57%
“…The first such model was that of Robert Blecker (1989), and it has been followed by contributions by Blecker (1999Blecker ( , 2011 again and by Hein and Vogel (2008). These kinds of models have been further extended to explicit two-country models in a number of ways, namely by Anton Rezai (2015), von Arnim et al (2014) as well as Capaldo and Izurieta (2013). Dutt (2015) is the first attempt at combining the Serrano approach with the neo-Kaleckian framework within an open-economy model.…”
Section: Introductionmentioning
confidence: 99%
“…whole is likely to have wage-led demand even if some countries have profit-led demand individually (Onaran and Galanis 2012;von Arnim et al 2014;Obst and Onaran 2016).…”
Section: Net Exportsmentioning
confidence: 99%
“…Razmi (2014) shows that stock-flow portfolio balance adjustments in an open economy that is subject to external constraints can make such an economy behave in a profit-led fashion in the medium run, even if it would be wage-led in the short run. Onaran and Galanis (2012), von Arnim et al (2014), and Obst and Onaran (2016) show that the impact of a redistribution between wages and profits can vary depending on whether the redistribution is limited to a single country or is global in nature. Palley (2016) shows that a redistribution of total labor income in favor of production workers' wages (at the expense of capitalist-managers' salaries) can be expansionary even in a system that is 'profit-led' overall.…”
Section: Introductionmentioning
confidence: 99%